Assessment of economic convergence among countries in the European Union - Szczepańska-Woszczyna, Katarzyna; Gedvilaitė, Dainora; Nazarko, Joanicjusz; Stasiukynas, Andrius; Rubina, Aleš (Technological and Economic Development of Economy, 2022)
The debate on the presence of economic benefits in the European Union (EU) is not over. The study responds unequivocally to this question, with the intensity of economic development in the countries that joined the European Union in 2004 and beyond twice as high as that of the countries that joined it this year, i.e. the EU’s old ones compared to the new ones; smoothness – 1.1 times and dynamics – 1.6 times. Another important trend for further development is that, as the level of economic development increases, its smoothness is diminishing. In respect of the context of the EP of all EU Members, it turned out that the higher intensity of enlargement was characterised by higher economic levels, with similar homogeneity and almost identical values for the dynamic indicator. The introduction to the article presents the context of the studies, i.e. two groups of EU Community countries are formed according to their level of economic development and the year of their accession to the Community, as well as a survey scheme. The literature review reveals the methods used to analyse the convergence of economic development in these countries, as members of the Community. The research methodology introduces the indicator of economic development of countries and provides a methodology for assessing its dynamics. The empirical part assesses the dynamics of economic development of both groups of countries and identifies trends in terms of convergence. The discussion section summarises the consolidation and destabilising factors in the EU and the importance of the study carried out in this context. The conclusions present the main results of the studies and outline their further directions. The results of the study can be used both in the EU and for the purpose-oriented decisions of its members on further economic development.